Teaching and Learning in Times of COVID-19: Uses of Digital Technologies During School Lockdowns - Pozo, Juan-Ignacio; Pérez Echeverría, María-Puy; Cabellos, Beatriz; Sánchez, Daniel L. (Frontiers in Psychology, 2021)
When schools closed because of COVID-19, teachers had to teach online. This paper intends to analyze the activities carried out during this time through digital technologies and the conceptions of teaching and learning that they reflect. We designed a Likert-type online questionnaire to measure the frequency of teaching activities. It was answered by 1403 primary and secondary education teachers in Spain. The proposed activities varied depending on the learning promoted (reproductive or constructive), the learning outcomes (verbal, procedural, or attitudinal), the type of assessment to which the activities were directed, and the presence of cooperative activities. The main result of this study was that teachers used reproductive activities more frequently than constructive ones. We also found that most activities were those favoring verbal and attitudinal learning. The cooperative activities were the least frequent. Finally, through a cluster analysis, we identified four teaching profiles depending on the frequency and type of digital technologies use: Passive, Active, Reproductive, and Interpretative. The variable that produced the most consistent differences was previous digital technologies use These results show that ICT uses are reproductive rather than constructive, which impedes effective digital technologies integration into the curriculum so that students acquire 21st-century competencies